Anion‐Conductive Membranes with Ultralow Vanadium Permeability and Excellent Performance in Vanadium Flow Batteries. Issue 2 (22nd January 2013) - Mai, Zhensheng; Zhang, Huamin; Zhang, Hongzhang; Xu, Wanxing; Wei, Wenping; Na, Hui; Li, Xianfeng
Abstract Anion exchange membranes prepared from quaternized poly(tetramethyl diphenyl ether sulfone) (QAPES) were first investigated in the context of vanadium flow battery (VFB) applications. The membranes showed an impressive suppression effect on vanadium ions. The recorded vanadium permeability was 0.02×10−7–0.09×10−7 cm2 min−1, which was two orders of magnitude lower than that of Nafion 115. The self‐discharge duration of a VFB single cell with a QAPES membrane is four times longer than that of Nafion 115. The morphological difference in hydrophilic domains between QAPES and Nafion was confirmed by TEM. After soaking the membranes in VO2+ solution, adsorbed vanadium ions can barely be found in QAPES, whereas the hydrophilic domains of Nafion were stained. In the ex situ chemical stability test, QAPES showed a high tolerance to VO2+ and remained intact after immersion in VO2+ solution for over 250 h. The performance of a VFB single cell assembled with QAPES membranes is equal to or even better than that of Nafion 115 and remains stable in a long‐term cycle test. These results indicate that QAPES membranes can be an ideal option in the fabrication of high‐performance VFBs with low electric capacity loss.